De Vlaamse Beweging en de patstelling van het Nederlands in de publieke overheid en het onderwijs in het jonge België (1830–1850) - Fabry, Jan (Acta Neerlandica, 2023)
Although the freedom of language use was anchored in the Belgian Constitution of 1831, in practice it led to almost complete Frenchification of public life, because civil servants could choose their own language. Dutch thus became the language of the countryside and the lower classes. Secondary and higher education were exclusively French speaking. The Flemish Movement came into being as a reaction to this. Cultural associations were founded and standards for Dutch language established. A petition in 1840 revealed the extent of the problem – the Flemish Movement demanded language equality and the establishment of a Flemish Academy. Although there was partial success in 1850 (Dutchification of primary and secondary education in Flanders), the petition also provoked a hostile reaction among French speakers who accused the Flemings of antibelgitude. The Flemish Movement therefore issued a pro-Belgian manifesto. But the government remained French speaking, so there was a stalemate.